Menjembatani Teks dan Konteks: Membangun Teologi Perjanjian Lama Kontekstual di Indonesia - Agustinus Setiawidi (Indonesian Journal of Theology, 2017)
Although efforts to construct Old Testament theology in Indonesia started in the 1970s, as attested in the number of theses and dissertations written by Indonesian scholars, the shape of contextual biblical theology itself remains dominated by a one-way model. The Bible is taken to be source, inspiration, evaluator, or teacher, while readers merely listen, imitate, and adhere to it. Yet readers today, who come from dynamically variegated contexts, are inevitably required to bridge-build between biblical texts and their own respective contexts. In view of this, dialogue in its broadest sense becomes the key to constructing a biblical theology overall, including OT theology. This paper challenges biblical theologians to find available approaches and, deploying them properly, to construct contextual Old Testament theology in Indonesia.